Impact of industrial nuclear emissions on nuclear explosion monitoring. (February 2023) - Miley, Harry S.; Eslinger, Paul W.
Abstract: In 1995, the development of a global radioactive xenon monitoring network was discussed in the Conference on Disarmament as part of a nuclear explosion verification regime. Discussions considered different network densities and different possible source magnitudes. The Comprehensive Nuclear Test Ban Treaty was subsequently written to initially include 40 locations for noble gas (radioxenon) samplers, and to consider using a total of 80 locations for noble gas samplers in its International Monitoring System (IMS) after the treaty enters into force. Since 2000, a global network of noble gas monitoring locations has been built as part of the IMS. This network, currently with 31 locations, is of sufficient sensitivity to discover that the Earth's atmosphere contains a complex anthropogenic radioactive xenon background. In this work, the impact of calculated xenon backgrounds on IMS radionuclide stations is determined by atmospheric transport modeling over a period of two years using global average values. The network coverage for potential nuclear explosions is based on a proposed method for finding anomalies among frequent background signals. Even with the addition of background radioxenon sources and using a conservative anomaly-based approach, this work shows that various network configurations have higher xenon coverage than the estimates developed when the IMS network was designed in 1995. While these global xenon coverage figures are better than expected when the network was designed in 1995, the regional impact of background radioxenon sources is large, especially for smaller source magnitudes from potential nuclear explosions, and in some cases the xenon background vastly reduces the coverage value of individual sampling locations. The results show the detection capability and presents an optimal installation order of noble gas sampling locations, e.g. from 40 to 80, after the treaty enters into force. Highlights: Nuclear reactor and medical isotope emissions still affect the explosion detection potential for releases above 10 14 Bq. Nuclear reactor and medical isotope emissions degrade the explosion detection potential for releases below 10 13 Bq. Reduced detection potential is strongly exacerbated in some regions by spatial gaps in the network. Strategically adding up to 40 sampling locations can improve knowledge of background sources.